Differentially enriched fungal communities in root rot resistant and susceptible varieties of tobacco (Nicotiana tabacum L.) under continuous monoculture cropping - Ao, Jincheng; Wang, Zheng; Yang, Qigang; Li, Bo; Li, Ying; Li, Yongmei (Frontiers in Microbiology, 2022)
Root rot (mainly caused by Fusarium spp.) is a major disease of tobacco that causes crop losses up to 15-20% of global tobacco production. The present study aimed to compare the fungal communities, and physicochemical properties of rhizosphere soil of two tobacco varieties. One variety was root rot resistant (Yunyan 87; Y) while other was root rot susceptible (Honghua Dajinyuan; H), each having four treatments of continuous monocropping cultures: control groups (HT0 and YT0); 2 years continuous cropping (HT2 and YT2); 4 years continuous cropping (HT4 and YT4); and 8 years continuous cropping (YT8 and HT8), respectively. The soil physicochemical properties including available nitrogen (AN), available phosphorus (AP), available potassium (AK), and organic matter (OM) were improved (p<0.05) from HT0 to HT8, whereas resistant variety (Y) showed an inconsistent trend from YT0 to YT8. The pH decreased (p<0.05) for both varieties in all cropping years. Further, the disease incidence rate and disease index of H variety also significantly (p<0.05) increased from HT0 to HT8. Alpha and beta diversity analyses revealed significant (p<0.05) differences between fungal communities of both rhizospheres. Overall susceptible variety had higher fungal diversity from HT0 to HT8, while resistant variety had lower diversity and higher similarities from YT0 to YT8. Ascomycota and Mortierellomycota were the dominant phyla in rhizosphere of both varieties having higher relative abundance in H and Y rhizosphere, respectively. Penicillium, Fusarium, and Chrysosporium were the top three abundant genera in both varieties with higher relative abundance of Penicillium and Chrysosporium in Y rhizosphere and Fusarium in H rhizosphere. Redundancy analysis revealed that fungal communities in H and Y rhizospheres were influenced by pH and carbon content, respectively. The top three highly enriched (p<0.05) pathways in both varieties (H and Y) were fatty acid elongation-saturated, fatty acid β-oxidation I, and glyoxylate cycle. Our study concluded that root rot resistant variety had more similar fungal community structure with relatively higher abundance of beneficial fungal taxa which sustained during continuous monocropping culture to suppress Fusarium root-rot.